HUBUNGAN DUKUNGAN SOSIAL DENGAN KESEJAHTERAAN SPIRITUAL MAHASISWA KEPERAWATAN - Wewengkang, Joel Marcelino; Tappy, Yunita (Fakultas Keperawatan, Universitas Klabat, 2026)
Nursing students are prepared to become professional nurses; however, during their education, they face various academic, emotional, social, and spiritual challenges that can impact their overall well-being. Social support and spiritual well-being are considered essential in helping students navigate these difficulties. This study aimed to analyze the relationship between social support and spiritual well-being among nursing students. A descriptive correlational design with a cross-sectional approach was employed. Sampling was conducted using quota sampling, selecting 25% of students from each academic level (Levels 1–4) at the Faculty of Nursing, Universitas Klabat, resulting in a total of 153 respondents. Data were collected in March 2025 using the Spiritual Well-Being Scale (SWBS) and the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis using Pearson correlation revealed a significant negative relationship between social support and spiritual well-being (r = -0.159; p = 0.048). These findings suggest that although students may receive social support, their spiritual well-being is more strongly influenced by their personal relationship with God. Further research utilizing qualitative approaches is recommended to explore in depth how individuals perceive and experience the connection between social support and spiritual well-being in their daily lives. Mahasiswa keperawatan dipersiapkan menjadi tenaga profesional yang kompeten, namun selama masa pendidikan mereka menghadapi berbagai tekanan akademik, emosional, sosial, dan spiritual yang dapat mempengaruhi kesejahteraan mereka. Dukungan sosial dan kesejahteraan spiritual dinilai berperan penting dalam membantu mahasiswa mengelola tantangan tersebut. Penelitian ini bertujuan untuk menganalisis hubungan antara dukungan sosial dan kesejahteraan spiritual pada mahasiswa keperawatan. Penelitian ini menggunakan desain deskriptif korelasional dengan pendekatan cross-sectional. Teknik pengambilan sampel dilakukan dengan metode quota sampling sebanyak 25% dari setiap tingkat (tingkat 1 hingga 4) di Fakultas Keperawatan Universitas Klabat, dengan jumlah responden sebanyak 153 orang. Data dikumpulkan pada bulan Maret 2025 menggunakan instrumen Spiritual Well-Being Scale (SWBS) dan Multidimensional Scale of Perceived Social Support (MSPSS). Analisis data menggunakan uji Pearson correlation menunjukkan adanya hubungan signifikan antara dukungan sosial dan kesejahteraan spiritual dengan arah korelasi negatif (r = -0,159; p = 0,048). Hasil ini mengindikasikan bahwa meskipun mahasiswa menerima dukungan sosial, kesejahteraan spiritual mereka lebih dipengaruhi oleh hubungan personal mereka dengan Tuhan. Diperlukan penelitian lanjutan dengan pendekatan kualitatif untuk menggali secara mendalam dinamika pengalaman individu terkait hubungan dukungan sosial dan kesejahteraan spiritual dalam kehidupan sehari-hari.